Synthesis, electrochemistry and in situ spectroelectrochemistry of novel tetra- and octa-substituted metallophthalocyanines bearing peripherally 4-(trifluoromethoxy)phenoxy groups - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
This study presents a series of peripherally tetra- and octa-substituted metallophthalocyanines [M = Zn (II), Co(II) and In(III)] derivatives bearing 4-(trifluoromethoxy)phenoxy groups on the peripheral positions. Characterization of the newly synthesized phthalocyanines has been performed by different spectroscopic techniques, such as FTIR, NMR and UV/Vis. The effect of the solvent nature on the aggregation behavior of the phthalocyanines was studied using different solvents, such as acetone, CHCl3, CH2Cl2 etc. The aggregation behavior of the phthalocyanine complexes was also examined in CH2Cl2 at different concentrations, ranging from 4 x 10(-6) to 14 x 10(-6) M. Electrochemical and spectroelectrochemical responses of the MPcs indicated the influence of the substituent environment to the redox features of the complexes, which were determined with cyclic and square wave voltammetry methods. The symmetrical octa-substitution of the complexes increased the aggregation ability and it also shifted the redox processes to more negative potentials. Moreover, the chemical and electrochemical reversibility of the electron transfer reactions decreased with the increasing the number of substituents. While ZnPcs and InPcs gave only Pc ring redox processes, metal-based reduction ([(CoPc2-)-Pc-II]/[(CoPc2-)-Pc-I](1-)) and metal-based oxidation ([(CoPc2-)-Pc-II]/[(CoPc2-)-Pc-III](1+)) processes of the CoPcs were observed in addition to the Pc based ones. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Aggregation behavior; Electrochemistry; Phthalocyanine; 4-Trifluoromethoxy)phenoxy; ANTIOXIDANT PROPERTIES; METAL PHTHALOCYANINES; THIN-FILMS; AGGREGATION; ZINC; FLUORESCENCE; SPECTROSCOPY; COBALT(II); SEPARATION; COMPLEXES